Pharmacokinetics of Asciminib When Taken With Imatinib or With Food. Issue 2 (5th October 2021) - Hoch, Matthias; Zack, Julia; Quinlan, Michelle; Huth, Felix; Forte, Sofia; Dodd, Stephanie; Aimone, Paola; Hourcade‐Potelleret, Florence
Abstract: Asciminib, a first‐in‐class, Specifically Targeting the Abelson kinase Myristoyl Pocket (STAMP) inhibitor with the potential to overcome resistance to adenosine triphosphate–competitive tyrosine kinase inhibitors, is being investigated in leukemia as monotherapy and in combination with tyrosine kinase inhibitors including imatinib. This phase 1 study in healthy volunteers assessed the pharmacokinetics of asciminib (40 mg single dose) under 2 conditions: when taken with imatinib (steady state; 400 mg once daily) and a low‐fat meal (according to imatinib prescription information), or when taken as single‐agent under different food conditions. Asciminib plus imatinib with a low‐fat meal increased asciminib area under the plasma concentration–time curve from time 0 to infinity and maximum plasma concentration (geometric mean ratios [90% confidence interval], 2.08 [1.93‐2.24] and 1.59 [1.45‐1.75], respectively) compared with asciminib alone under the same food conditions. Asciminib plus food decreased asciminib area under the plasma concentration–time curve from time 0 to infinity compared with asciminib taken under fasted conditions (geometric mean ratios: low‐fat meal, 0.7 [0.631‐0.776]; high‐fat meal, 0.377 [0.341‐0.417]). Asciminib plus imatinib was well tolerated with no new safety signals. Overall, coadministration of asciminib with imatinib and a low‐fat meal results in a moderate increase in asciminib exposure compared with asciminib alone under the same food condition. Food itself decreases asciminib exposure, indicating that single‐agent asciminib should be administered in the fasted state to prevent potential suboptimal exposures.